Research on an intelligent vibration detachment system for rotary tiller based on soil surface roughness dynamic characteristics - Liu, Guoyang; Zheng, Kan; Xia, Junfang; Cheng, Jian; Liu, Zhengyuan; Wei, Youshuai; Zhang, Beihai; Zhang, Peng (Computers and electronics in agriculture, 2024)
[Display omitted] •The relationship between soil surface roughness and fractal dimension was explored.•Soil surface roughness is used as a basis to regulate rotary tiller detachment.•An intelligent vibration detachment system for rotary tiller was developed.•The developed system can improve the tillage quality and reduce soil adhesion. The adhesion and winding problem between the rotary roller and the soil and straw stubble severely affect the quality of the tillage operation. In response to the practical requirements of adhesion reduction and detachment increment of rotary tiller in paddy fields, our study develops an intelligent vibration detachment system for rotary tiller based on soil surface roughness (SSR) dynamic characteristics. The working principle of the system is that the camera module captures the soil surface image after tillage and calculates the fractal dimension of the image. Based on the functional relationship model between fractal dimension and SSR parameters (root mean square height), the SSR results are obtained and fed back to the system for comparison with the preset SSR values. When the actual measured SSR is greater than the preset value due to soil adhesion and straw winding, the system issues a command to control the excitation device for rotary roller vibration detachment. To verify the superiority and reliability of the developed system, the comparative experiments were conducted via three types of tillage tools in paddy fields: a traditional rotary tiller (TT), a rotary tiller with the developed system (IDT) in this study, and a rotary tiller with mechanical detachment method (MDT). Taking the relevant indexes of TT as a reference, IDT improved by 29.45%, 6.43%, 14.19%, 6.30%, 7.90%, and 6.83% compared with MDT in terms of the improvement effect of these indexes such as adhesion mass, tillage depth stability coefficient, soil surface roughness, soil distribution uniformity, straw buried rate and soil broken rate. Adopting the adhesion mass as the index for judging the detachment performance, IDT has excellent adhesion reduction and detachment ability for high straw stubble and wet soil, and MDT has better anti-winding performance than TT. The indexes other than these were used to indicate the operation quality, with IDT being better than the other two, followed by MDT and TT being the worst. The experimental results showed that the developed system could enable the rotary tiller to make the corresponding detachment response according to the SSR dynamic characteristics, effectively improving the operation quality and detachment performance of the rotary roller, with high detachment efficiency and controllability. The results of the study contribute to realizing intelligent adhesion reduction and detachment increment of rotary tiller in paddy fields, which could provide theoretical reference for the optimization design of tillage equipment to improve quality and efficiency.